Cardiovascular Autonomic Function in Individuals with Rheumatoid Arthritis - Deshpande, Dr. Pranjali; Howale, Dr. Deepak S. (International Journal of Innovative Research in Medical Science, 2018)
Rheumatoid arthritis is common inflammatory arthritis arising throughout the world. A chronic systemic inflammatory autoimmune disorder is known as Rheumatoid arthritis (RA). Principally it affects the joints and usually accompanied by one or more of extra-articular manifestations as rheumatoid nodules, neuropathy and norm chromic normocytic anemia. Rheumatoid arthritis can start at any age, but has maximum between 35 to 55 years of age. The prevalence of RA is about 1% worldwide whereas India is 0.9% with women suffering 3-5 times more than men. Sympathetic and parasympathetic involvement has described in primary and secondary vasculitis processes, as in systemic vasculitis processes like: SLE, RA. Peripheral nervous system is the main target in RA patients where as involvement of central nervous system (CNS) is rare. The aim of this study was to evaluate cardiac autonomic function in RA and compare with healthy individuals by using HRT analysis. Materials and Methods: A cross-sectional study was performed which was carried out in the Dept. of Physiology at Zydus Medical College and Hospital. It was carried out on both males and females of mean age group 45±10 years to study autonomic functions in RA. Total 50 individuals were include in which 25 were included as healthy individuals with not on any medication, served as controls and 25 were diagnosed with RA, on the basis of criteria developed by American College of Rheumatology along with sex matched controls. Details of history and examination were recorded on Performa. Patients were examined for signs and symptoms of possible Autonomic Nervous System (ANS) dysfunctions. Result: 50 individuals were include in this study which were grouped into Study group (Group – A) and Control group (Group – B). Group – A consisted of 25 individuals who were diagnosed with rheumatoid arthritis on basis of criteria developed by American College of Rheumatology. Group – B consisted of 25 healthy individuals not on any medication as to explain normal changes. The 30:15 ratio and valsalva maneuver demonstrated a less decrease but was non-significant statistically in the patients with Rheumatoid Arthritis as compared to control (p>0.05). On standing the blood pressure response the change in diastolic blood pressure was significantly (P<0.01) lower in groups A as compared to control. Conclusion: Cardiovascular autonomic function tests in routine clinical examination helpful in early detection of autonomic dysfunction in this disease. Further comprehensive information are useful about autonomic function may be extracted from global evaluation of all tests performed. Therefore testing of autonomic function may be the part of routine clinical evaluation in RA to reduce the cardiovascular autonomic morbidity.